Drug reaction with eosinophilia and systemic symptoms (DRESS) caused by sulfasalazine: a case report and literature review - A. S. Fedorov; Yu. O. Savelyeva; Yu. Yu. Grabovetskay; L. A. Rudyuk; E. M. Kuchinskaya; M. M. Kostik (Современная ревматология)
Drug-induced hypersensitivity syndrome (DIHS) or drug reaction with eosinophilia and systemic symptoms (DRESS) is a rare, potentially fatal systemic reaction characterized by multiorgan damage involving the liver, hematopoietic system and skin, and heterogeneous manifestations of fever, rash, lymphadenopathy and eosinophilia with unpredictable course.We describe a 41-year-old female patient who developed DRESS syndrome after taking sulfasalazine prescribed for non-radiographic axial spondyloarthritis. Treatment with intravenous and then oral glucocorticoids was effective. A review of the literature on this topic is presented.